(untitled) (Nordic Journal of African Studies, 2011)
This paper seeks to describe some linguistic features of six dialects of the so-called Meru group. All the six are found on a geographical continuum and they are mutually intelligible. The argument in this paper is that the linguistic features, e.g. phonological, morphological and lexical systems of dialects, are largely responsible for reduced degrees of intelligibility. Dialect clusters within a given geographical area exhibit common phonological characteristics for that particular cluster. Besides this sharing of phonological characteristics, there exist features that are peculiar to individual dialects. That is, there are idiosyncratic features inherent in a given dialect that set it off from the other dialects in the same cluster. The existences of these peculiar features, therefore, enable us to draw dialect boundaries from a phonological point of view. Morphological features as well as lexical differences that are unique to one dialect also provide a firm basis for drawing linguistic boundaries. The total of these diversities in unity constitute a language continuum. The dialects maintain individual characteristics, though some may seem simple, to set them off from one another.